Green infrastructure as a Nature-based Solution for mitigating impacts on urban drainage in São Paulo: a mapping of the literature - Moniz, Daniela; Sant’Ana, Daniel (Revista de Tecnologia & Gestão Sustentável, 2024)
The disorganized growth of the city of São Paulo, with the occupation of floodplains, the canalization of rivers and streams and waterproofing, has caused several problems in the city, including floods and recurrent flooding during heavy rainfall events. As a way of solving the problem, the public authorities have come up with rainwater detention reservoirs, known as ’piscinões’, which reduce the volume of water in the drainage network, but dispose of the rainwater and with it all the pollution that reaches it. Based on an exploratory literature review, this article sought to map the main studies carried out on green infrastructure as a nature-based solution for urban drainage in São Paulo and, with this, to verify its applicability in the search for solutions to adapt the city. The studies showed good results in the implementation of green infrastructure for urban drainage, but some of them found errors in design or execution. In addition, even though the government indicated in the revision of the Master Plan that the drainage system should prioritize nature-based solutions, the solution adopted for the city’s flooding problems is the installation of “piscinões”.